LEMAHNYA MUTU KUALITAS INFRASTRUKTUR LOGISTIK DI INDONESIA BERDAMPAK PADA PEREKONOMIAN NASIONAL - Muhamad Nur Fajar; Adam Fikri; Muhammad Thoriq Arkan; Siti Sahara (Cross-border, 2023)
Indonesia's logistics facilities can be said to be far from qualified. Compared to other countries,the quality and quality of logistics in Indonesia can be said to be very weak. One of the main factors causing Indonesia's weak logistics is the deplorable condition of the roads. Weak logistics in Indonesia has an impact on the national economic. Based on data quoted from the LPI (Logistic Performance Index), it can be seen that in 2018, Indonesia has an LPI of 3.15. This makes Indonesia ranked backward within the scope of ASEAN, which is ranked 5th and ranked 46th out of 160 member countries of the World Bank. The results of the discussion in this journal will focus on the weak quality of logistics facilities in Indonesia so that conclusions can be drawn in the form of efforts to improve the quality of logistics facilities with the aim of avoiding further impacts on the economy of society and the country. In writing, this journal uses descriptive qualitative research methods using books, journals and websites related to the topic of discussion, by practicing literature study data collection techniques.